Emissions performance of high moisture wood fuels burned in a residential stove. (1st March 2019) - Price-Allison, A.; Lea-Langton, A.R.; Mitchell, E.J.S.; Gudka, B.; Jones, J.M.; Mason, P.E.; Williams, A.
Highlights: Combustion of wood with different moisture content was studied in a domestic stove. Moisture content influences the burning rate and the emissions. High moisture content fuels will result in increased particulate emissions. High moisture content leads to higher levels of brown carbon emission. NOX is mainly influenced by the fuel-N content in these small capacity stoves. Abstract: A study has been made of the effect of fuel moisture content on emissions from a wood burning domestic stove. Two fuel types were studied: beech which is a hardwood, and spruce which is a softwood. The moisture contents investigated were for a freshly felled wood, a seasoned wood and a kiln dried wood. The effect of the moisture measurement method was considered using a commercial electrical conductivity probe moisture meter which was compared with laboratory analysis by drying in an oven at 105 °C. It was shown that the probe can significantly underestimate the actual moisture content in certain cases. Correlations were made of the burning rate, the Emission Factors for the formation of gaseous and particulate pollutants as a function of the moisture content. We also studied the ratio of Black Carbon to Total Carbon (BC/TC) to obtain information on the organic content of the particles. The NOX emissions from this type of stove were only dependent on the fuel-nitrogen content and not on the moisture content.